التضاد الصرفي في القرآن الكريم وموقف أبي حيان الأندلسي منه - كرام, قمرة; محلو, عادل (جامعة الوادي - University of Eloued, 2016)
يعد التضاد الصرفي فرعاً من فروع ظاهرة التضاد في اللغة العربية وسببا من أسبابها، ويقتصر في مدلوليه على تضاد دلالة الصيغة الصرفية كالفاعلية والمفعولية. إذ كثيرا ما تتحد الدلالتان في صيغة صرفية واحدة، خاصة إذا تعلّق الأمر بمعاني القرآن واجتهاد المفسرين في ذلك. وفي هذه الدراسة بيان لمواضع التضاد الصرفي في البحر المحيط لأبي حيان الأندلسي [ت745ه]، مرتبة حسب نوع الصيغة الصرفية ودلالتها. Abstract: Morphological contrast is , both, a branch of the phenomenon of contrast in Arabic and one of its causes. In significance, it is restricted to the contrast in meaning of the verbal formula such as subjective and objective case; both opposite meanings are expressed by the same verbal formula. This is, mainly the case when referring to the meaning of The Holy Quran and the interpreters’ efforts in extracting its significance. This study tries to highlight the cases of morphological contrast in “Albahr Almohit”, by Abu Hayyan Al Andaloussi [745 h], arranged according to the type of their morphological structure and its significance.
مقال
Keywords: التضاد؛ الصرفي ؛ القرآن الكريم ؛ موقف ؛أبي حيان الأندلسي